Relationship between the announcement of administrative sanctioning proceedings and CEO turnover - Guimarães, Rinaldo de Sousa (2023)
This research aims to investigate the likelihood of forced CEO turnover in Brazil, based on the announcement of administrative sanctioning proceedings (PAS) conducted by the Brazilian Securities Commission (CVM). For this purpose, a sample of 272 Brazilian firms listed on the Brazilian Exchange B3 (Brasil, Bolsa, Balcão) and 121 PAS initiated and judged by CVM were considered from the period between 2011 and 2021. The analyses were conducted with the statistical techniques of binary and multinomial logistic regressions. The results indicate that the initiation – and subsequent announcement to the market – of PAS to investigate potential irregularities by economic agents in Brazilian listed companies increase the likelihood of CEO turnover. When analyzing heterogeneities in the types of CEO turnover analyzed, voluntary CEO turnover is more often, and no effects were perceived on the likelihood of forced CEO turnover compared to the likelihood of no turnover).